Threshold-dominated deceleration of Aeolian activity in the Badain Jaran Sand Sea: the role of reduced strong wind events and local thermal control - Yang Qinghua; Cheng Hongyi; Zhao Liqiang; Yang Linhai; Liu Yi (Aeolian Research, 2026)

Topographic modulation of lagged dust activity in the southeastern Tibetan Plateau during the Last Glacial Period - Yixiao Han; Yougui Song; Linhai Yang; Liangqing Cheng; Mingyu Zhang; Minwen Lan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Climate-induced forest destabilization and shrub stabilization in Africa - Linhai Cheng; Qiang Tang; Nan Lu; Yafeng Wang; Changjia Li; Shuai Wang; Xiangyi Li; Phuping Sucharitakul; Yongzhe Chen; Zhihong Xu; Lindsay C. Stringer; Bojie Fu (Global and Planetary Change, 2026)

Release and redistribution of rare earth elements from coal ash in simulated landfill systems - Linhai Ye; Zhengyu Wang; Feng Chen; Xu Xing; Cheng Zeng; Tao Zhou; Youcai Zhao (Environmental Pollution, 2026)

Improving resilience monitoring in non-stationary systems via a robust data-chunking algorithm - Linhai Cheng; Qiang Tang; Nan Lu; Chi Xu; Babak M.S. Arani; Changjia Li; Yafeng Wang; Xiangyi Li; Phuping Sucharitakul; Shuai Wang; Jie Wei; Junran Li; et al. (Science Bulletin, 2026)

Theoretical approach for predicting vertical deformation of underlying shield tunnels due to excavation unloading, incorporating soil consolidation - Cheng Dong; Mingjie Jiang; Liang Xiao; Linhai Lv; Yongkai Ji; Yubo Liu; Guoxiong Mei (Transportation Geotechnics, 2026)

High-resolution luminescence chronology for the late Holocene loess at the northern piedmont of Kunlun Mountains in arid central Asia and its paleoenvironmental implications - Lisha Wu; Linhai Yang; Jibao Dong; Jun Peng; Jingran Zhang; Peng Cheng (Quaternary Geochronology, 2026)

Discovery and implications of the Late Carboniferous Tasensu gabbro–gabbrodiorite–granodiorite–monzogranite bimodal intrusions in Xiwuqi, Inner Mongolia, China - Wenjing Yang; Tianshe Cheng; Xuebin Zhang; Xiangqian He; Guoping Wang; Xujiang Cheng; Linhai Wang; Lijun Guo; Xingfang Duo; Hongsheng Gao (Journal of Volcanology and Geothermal Research, 2026)

The effects of temperature on the nutritional quality of crayfish (Procambarus clarkii) were analyzed by combining transcriptome, metabolome and intestinal microbiota - Ruichun Li; Wenqi Qian; Li Huang; Shuyan Bai; Chenhui Li; Ningning Du; Long Cheng; Lei Xiu; Linhai Yu; Tao Guan; Jian Li; Shilong Chen; et al. (Food Bioscience, 2025)

Mountain glaciers regulate the response of Tibetan Plateau dust activity to global climate change during the last glacial - Liangqing Cheng; Hao Long; Linhai Yang; Jingran Zhang; Yougui Song; Zhong Chen; Yubin Wu; Zhibao Dong (Quaternary Science Reviews, 2025)

Global potential for regime shifts among shrubland, grassland, and forest - Zhuoran Qu; Xiaoyan Li; Sha Zhou; Yuanhong Deng; Chao Yang; Fangzhong Shi; Linhai Cheng (Global and Planetary Change, 2025)

Yttrium-catalyzed growth of enriched (6, 4) and (6, 5) carbon nanotubes for their high-efficiency separation - Xuan Lv; Linhai Li; Zhaoyang Han; Qianru Wu; Fangfang Cheng; Mengyu Wang; Guodong Xu; Huaping Liu; Maoshuai He (Chemical Engineering Journal, 2025)

Alternating dominance of Westerlies and East Asian winter monsoon on dust activities across the northeastern Qinghai-Tibet Plateau since 18.5 ka - Hao Long; Yun Cai; Jingran Zhang; Liangqing Cheng; Linhai Yang; Hongyi Cheng (Global and Planetary Change, 2025)

FYB1-targeted modulation of CAPG promotes AML progression - Wenyuan Liu; Hongli Yin; Zhiwei Xie; Fang Fang; Jinhua Chu; Linhai Yang; Lingling Huang; Songji Tu; Huaju Cai; Zhengyu Wu; Anbang Wei; Chengzhu Liu; et al. (Molecular and Cellular Biochemistry, 2025)
Acute myeloid leukemia (AML) is a rare and heterogeneous disease. Over the past few decades, patient prognosis has improved with continuous improvements in treatment, but outcomes for some patients with primary drug resistance or relapse after treatment remain poor. Additional therapies to improve outcomes for these patients are urgently needed. FYB1 expression differs substantially between AML tissues and normal tissues. High FYB1 expression is correlated with poorer overall survival (OS), indicating that FYB1 may regulate AML progression. Therefore, understanding the effect of FYB1 on AML could improve the success rate of therapeutic approaches and prognosis for patients with AML. In this study, through analysis of large databases and both in vivo and in vitro experiments, we assessed the expression and role of FYB1 in AML and the relationship of FYB with patient prognosis. Downstream targets of the FYB1 gene were analyzed by RNA-seq. Database mining and in vitro experiments were used to further clarify the effect of the downstream target gelsolin-like actin-capping protein (CAPG) on AML cells and its relationship with patient prognosis. FYB1 expression was significantly higher in AML tissue and corresponded with a poor prognosis. FYB1 knockdown inhibited AML cell proliferation, promoted cell apoptosis, reduced cell adhesion capability and significantly reduced the tumor formation rate in mice. In addition, FYB1 knockdown induced a notable decrease in CAPG expression. The suppression of CAPG significantly inhibited cell proliferation and increased cell apoptosis. The conclusions of this study underscore the pivotal role of the FYB1/CAPG axis in promoting AML. We propose that the FYB1/CAPG axis could serve as a new thread in the development of therapeutic strategies for AML.

Reconstructing the late Quaternary soil erosion and dust deposition dynamics in the southern Loess Plateau: Insights from Lake Luyanghu sedimentary records - Hongfei Zhao; Xin Zhou; Linhai Yang; Hao Long; Liangqing Cheng; Yonghao Yan; Jie Zhou; Qianli Sun; Claudio O. Delang; Hongming He (Quaternary Science Reviews, 2024)

Retreating ice sheet caused a transition from cold-dry to cold-humid conditions in arid Central Asia - Liangqing Cheng; Hao Long; Jingran Zhang; Yubin Wu; Jun Cheng; Linhai Yang; Hongyi Cheng (Quaternary Science Reviews, 2024)

Association between sleep quality and living environment among Chinese older persons: a cross-sectional study - Yan Wang; Mengjie Guo; Jianan Li; Yan Zhang; Jing Cheng; Linhai Zhao; Lidan Wang; Guixia Fang; Guimei Chen; Zhongliang Bai; Han Liang; Ren Chen; et al. (Sleep and Biological Rhythms, 2024)

Nanobubble water promotes anaerobic digestion of high-solids cattle manure under mesophilic and thermophilic conditions - Qingfang Zhang; Ruoyu Wu; Ziying Xu; Yutong Feng; Cheng Peng; Hailong Shi; Yuqian Zhang; Linhai Yang; Dan Luo; Peng Dong; Wenqi Gao; Tianfeng Wang (Environmental Research, 2024)

Three-dimensional Biot consolidation solution of adjacent aquitards induced by regional drawdown of the water table - Weijie Cheng; Weitao Yang; Linhai Lv; Cheng Dong; Zhongming Xie; Guoxiong Mei (Computers and Geotechnics, 2024)

Intermittent energization improves anaerobic digestion of microbial electrolysis cell-assisted nitrogen-rich sludge under mesophilic and thermophilic conditions - Qingfang Zhang; Cheng Peng; Jiajia Pu; Yutong Feng; Hong Zhu; Miaozhi Yang; Ziying Xu; Yuqian Zhang; Linhai Yang; Dan Luo; Tianfeng Wang (Journal of Environmental Chemical Engineering, 2024)

Are multiple ecosystem stability metrics equally sensitive and consistent to environmental gradient? A test for African terrestrial biomes - Linhai Cheng; Nan Lu; Bojie Fu; Zhihong Xu (Global and Planetary Change, 2023)

The implications of N6-methyladenosine (m6A) modification in esophageal carcinoma - Cheng He; Xiao Teng; Luming Wang; Miaoqi Ni; Linhai Zhu; Jiacong Liu; Wang Lv; Jian Hu (Molecular Biology Reports, 2023)
Esophageal carcinoma (EC) is always diagnosed at advanced stage and its the mortality rate remains high. The patients usually miss the best opportunity for treatment because of non-specific symptoms and the survival rates are low. N6-methyladenosine (m6A) the predominant modification in eukaryotic messenger RNA(mRNA), serves vital roles in numerous bioprocess. This chemical modification is dynamic, reversible and consists of three regulators: m6A methyltransferases (writers), demethylases (erasers) and m6A-binding proteins (readers). Recently, a growing number of evidences have indicated relationships between m6A and EC. Whereas, lacking of cognition about the molecular mechanism of m6A modification in esophageal carcinoma. We will focus on the biological function roles of m6A modification in the tumorigenesis and development of EC. Recent studies showed that immunotherapy had a positive impact on EC. The relationship between m6A and immunotherapy in EC deserves further research and discussion. We will also discuss the potential clinical applications regarding diagnosis, treatment and prognosis of m6A modification for EC and provide perspectives for further studies.

Late Holocene change in South Asian monsoons and their influences on human activities in the southern Tibetan Plateau - Liangqing Cheng; Linhai Yang; Hao Long; Jingran Zhang; Xiaodong Miao; Yubin Wu; Minwen Lan; Yougui Song; Zhibao Dong (CATENA, 2023)

Early Holocene dust activity variation in the southern Tibetan Plateau and its response to solar irradiance - Liangqing Cheng; Linhai Yang; Hao Long; Yougui Song; Zhong Chen; Minwen Lan; Mengping Xie; Zhibao Dong (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Milankovitch-paced South Asian monsoons during Marine Isotope Stage 5 - Liangqing Cheng; Linhai Yang; Hao Long; Yougui Song; Xiaodong Miao; Jingran Zhang; Yubin Wu; Minwen Lan; Mengping Xie; Zhibao Dong (Global and Planetary Change, 2023)

The Clinical Study of the Optimalization of Surgical Treatment and the Traditional Chinese Medicine Intervention on Palmar Hyperhidrosis - Yong Yang; Zhikun Yan; Xiaoqing Fu; Liwen Dong; Linhai Xu; Jun Wang; Genmiao Cheng (Cell Biochemistry and Biophysics, 2014)

Image misalignment caused by decimation in image fusion evaluation - Linhai Jing; Qiuming Cheng; Huadong Guo; Qizhong Lin (International Journal of Remote Sensing, 2012)

An image fusion method based on object-oriented classification - Linhai Jing; Qiuming Cheng (International Journal of Remote Sensing, 2012)

Spectral change directions of multispectral subpixels in image fusion - Linhai Jing; Qiuming Cheng (International Journal of Remote Sensing, 2011)

An image fusion method taking into account phenological analogies and haze - Linhai Jing; Qiuming Cheng (International Journal of Remote Sensing, 2011)

An image fusion method for misaligned panchromatic and multispectral data - Linhai Jing; Qiuming Cheng (International Journal of Remote Sensing, 2011)

A technique based on non-linear transform and multivariate analysis to merge thermal infrared data and higher-resolution multispectral data - Linhai Jing; Qiuming Cheng (International Journal of Remote Sensing, 2010)

Two improvement schemes of PAN modulation fusion methods for spectral distortion minimization - Linhai Jing; Qiuming Cheng (International Journal of Remote Sensing, 2009)